An evaluation of a pilot multi-professional offender personality disorder (OPD) higher education programme. Issue 2 (31st March 2022) - Lamph, Gary; Elliott, Alison; Gardner, Kathryn; Wright, Karen; Jones, Emma; Haslam, Michael; Graham-Kevan, Nicola; Jassat, Raeesa; Jones, Fiona; McKeown, Mick
Abstract : Purpose: Workforce development is crucial to the offender personality disorder (OPD) service to provide contemporary, evidenced care and treatment. This study aims to provide an overview and the research evaluation results of a regional higher education programme delivered to a range of criminal justice workers used on the OPD pathway. Design/methodology/approach: Three modules were developed and delivered; these are (1) enhancing understanding (20 students), (2) formulation and therapeutic intervention (20 students) and (3) relationships, teams and environments (17 students). A mixed-methods study evaluated participant confidence and compassion. Pre, post and six-month follow-up questionnaires were completed. Additionally, a series of focus groups were conducted to gain in-depth qualitative feedback with a cross-section of students across the modules ( N = 7). Quantitative data was collected and analysed separately due to the three modules all having different content. Qualitative data was analysed, and a synthesis of qualitative findings was reported from data taken across the three modules. Findings: A total of 52 students participated, drawn from three modules: Module 1 ( N = 19); Module 2 ( N = 18); Module 3 ( N = 15). Confidence in working with people with a personality disorder or associated difficulties improved significantly following completion of any of the modules, whereas compassion did not. Results have been synthesised and have assisted in the future shaping of modules to meet the learning needs of students. Research limitations/implications: Further evaluation of the effectiveness of educational programmes requires attention, as does the longer-term durability of effect. Further research is required to explore the post-training impact upon practice, and further exploration is required and larger sample sizes to draw definitive conclusions related to compassion. Practical implications: This unique model of co-production that draws upon the expertise of people with lived experience, occupational frontline and academics is achievable and well received by students and can be reproduced elsewhere. Social implications: The positive uptake and results of this study indicate a need for expansion of accessible OPD workforce training opportunities across the UK. Further research is required to explore student feedback and comparisons of effectiveness comparing different modes of training delivery, especially in light of the pandemic, which has forced organisations and higher education institutions to develop more digital and distance learning approaches to their portfolios. Originality/value: This novel research provides an evaluation of the only higher education credit-bearing modules in the UK focussed solely upon the OPD workforce and aligned with the national drive for non-credit bearing awareness level training "knowledge and understanding framework" (KUF).